The Relationship of Fear of Missing Out and Self-Control in Students Using Social Media - Rifqi Rifani; Eka Sri Handayani; Yulizar Abidarda (Grief and Trauma, 2025)
The intensive use of social media has become common among students at SMAN 8 Banjarmasin, where many students use social media daily. This phenomenon highlights the importance of investigating psychological factors influencing social media usage, particularly Fear of Missing Out (FOMO) and self-control. This study examines the relationship between FOMO and self-control on social media usage among Grade X students at SMAN 8 Banjarmasin. This research employed a quantitative approach with a correlational research design. The instrument used was a questionnaire that had been tested for validity and reliability. Data collection was carried out by distributing the questionnaires directly to the respondents. The results showed that the Fear of Missing Out variable positively and significantly affected social media usage. In contrast, the Self-Control variable negatively and significantly affected social media usage among Grade X students at SMAN 8 Banjarmasin. Overall, 52.4% of the variance in social media usage is influenced by the Fear of Missing Out and Self-Control variables. Based on these findings, it is recommended that schools and parents pay greater attention to strengthening students’ self-control and providing education on healthy social media use to minimize the negative impacts of Fear of Missing Out.